The Poverty of Policy Execution: The Nigerian Experience (British Journal of Multidisciplinary and Advanced Studies, 2024)
Policy summersault in Nigeria has to a large extent eroded public confidence in government’s ability to provide essential service as a way of solving societal problems. There is greater attention being paid to public policy execution in and out of intellectual discourse. The concept of public policy execution is not without its attending challenges and creative process of getting it done. Thus various proposals are faced with difficulties enroute execution. Various proposals fail to materialise, while those that do appeared distorted or mutilated, for them not to serve their envisioned drives. This paper objectively examines the challenges of policy execution in Nigeria. The paper relies on primary and secondary data for analysis and presentation these underlying factors. The paper found that effective policy execution can only be attained through unceasing commitment politically with clear responsibilities definition and effective coordination, by ensuring that genuinely, commitment to elimination of corruption at all levels of government is achieved for free flow of policy execution process. The paper concluded that poverty of policy execution is premised on government genuine commitment